Generation of spatially nonuniform ground motion for nonlinear analysis of a concrete arch dam. - Alves, S.W.
An accelerometer array at Pacoima Dam with three locations along the base and abutments recorded ground motion from a magnitude 4.3 earthquake on 13 January 2001. These records present an opportunity to study spatial nonuniformity for the motion in a canyon. Topographic amplification is characterized by ratios of response spectral displacement between locations, and seismic wave travel times are studied using cross-correlation functions to obtain delays. Results of the analysis of the 2001 earthquake records are used to generate ground motion for the 1994 Northridge earthquake to replace records that were not able to be fully digitized. The ground motion generated for the Northridge earthquake is used as input to a finite element model of Pacoima Dam. The response of the model is consistent with observations of Pacoima Dam after the Northridge earthquake. Comparison of the response due to nonuniform input with the response due to uniform input demonstrates the importance of accounting for spatial nonuniformity because of the significance that the pseudostatic component has for the response to nonuniform input.
Keywords: Pacoima Dam; Spatially nonuniform ground motion; Pseudostatic response; Generated abutment motion; Northridge earthquake; Finite element analysis